DIGITAL POLICY IN THE AGRICULTURAL SECTOR OF KAZAKHSTAN - IMPLEMENTATION DEFICIT - Beisenbekova, Sandugash (Nazarbayev University Graduate School of Public Policy, 2022)
Digitalization of the agriculture sector is one of Kazakhstan's most intractable policy challenges. Nevertheless, digitalization needs amongst farmers reliant on subsidies have remained high during the policy implementation period 2018-2022. This reflects a persistent but complex 'implementation deficit' as evidenced by the regional managers' failure to meet the digital policy targets set by decision-makers and contradictions between the type of digital solutions installed and policymakers' plans. To illuminate the factors which have shaped the implementation deficit, this dissertation draws on Matland's model on the influence of conflict and ambiguity on policy implementation. The research uses qualitative interpretive research to explore the digital implementation issue via semi-structured interviews, documentary analysis, and participant observation. The dissertation reveals that digital policy is associated with highly ambiguous policy goals, policy implementation mechanisms, and high conflict of goals. This is not surprising because street-level bureaucrats of the hierarchical administration system covertly sabotaged the bottom-up approach of the decision-makers due to a lack of policy capacity. The opposition of values between decision-makers and the street-level bureaucrats has shaped the scale and nature of the digital policy implementation deficit. The key contribution of the research is that it extends Matland's model in the application to the developing countries context. Namely, this dissertation uncovers the incompatibility of the "bottom-up" approach in developing countries' contexts associated with highly hierarchical administration systems and the dominance of informal institutions given low policy capacity. In addition, the dissertation research highlights competing for goals between the "bottom-up approach" of decision-makers and the need for the "quick progress" of street-level bureaucrats. The dissertation's findings question the appropriateness of the "bottom-up approach" in the condition of poor policy capacity of the street-level bureaucrats, lack of an evaluation system, and tunnel vision in the public manager's workplace
Keywords: type of access: open access